1996
DOI: 10.1146/annurev.micro.50.1.213
|View full text |Cite
|
Sign up to set email alerts
|

REGULATION OF PECTINOLYSIS IN ERWINIA CHRYSANTHEMI

Abstract: Erwinia chrysanthemi is an enterobacterium that causes various plant diseases. Its pathogenicity results from the secretion of pectinolytic enzymes responsible for the disorganization of the plant cell wall. The E. chrysanthemi strain 3937 produces two pectin methylesterases, at least seven pectate lyases, a polygalacturonase, and a pectin lyase. The extracellular degradation of the pectin leads to the formation of oligogalacturonides that are catabolized through an intracellular pathway. The pectinase genes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
308
1
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 369 publications
(321 citation statements)
references
References 155 publications
2
308
1
5
Order By: Relevance
“…Induction in the presence of pectin derivatives mainly results from the interaction of the KdgR repressor with intracellular pectic catabolites such as and 5-keto-4-deoxyuronate or 2-keto-3-deoxygluconate (2). A 10-fold increase in the fusion expression in a kdgR background (Table III) confirmed that the kdgM expression is controlled by the main regulator of genes involved in pectin degradation, KdgR (2,41,47). However, the expression of the fusion in a kdgR mutant is still induced by GA. Transcriptional regulation of genes involved in pectin and GA degradation pathways is independent.…”
Section: Kdgm Is a Major Outer Membrane Protein Of Pectinolyticmentioning
confidence: 58%
See 4 more Smart Citations
“…Induction in the presence of pectin derivatives mainly results from the interaction of the KdgR repressor with intracellular pectic catabolites such as and 5-keto-4-deoxyuronate or 2-keto-3-deoxygluconate (2). A 10-fold increase in the fusion expression in a kdgR background (Table III) confirmed that the kdgM expression is controlled by the main regulator of genes involved in pectin degradation, KdgR (2,41,47). However, the expression of the fusion in a kdgR mutant is still induced by GA. Transcriptional regulation of genes involved in pectin and GA degradation pathways is independent.…”
Section: Kdgm Is a Major Outer Membrane Protein Of Pectinolyticmentioning
confidence: 58%
“…E. chrysanthemi possesses aspecific porins similar to the OmpF and OmpC porins of E. coli, which are responsible for membrane permeability for molecules of Ͻ600 Da (14). Such porins could be responsible for GA 2 and GA 3 uptake (GA 3 is 546 Da) but not for the uptake of larger GA n . When grown in the presence of GA n (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations